PHYSIOLOGICAL PERFORMANCE OF COMMON BEANS SUBMITTED TO DEFICIT IRRIGATION AND BIOSTIMULANTS - Galvão, Ícaro Monteiro [UNESP]; Dos Santos, Osvaldir Feliciano [UNESP]; DE SOUZA, Mara Lúcia Cruz [UNESP]; DE OLIVEIRA, Dariane Priscila Franco [UNESP]; DE ANDRADE, Tamiris Cristina Oliveira [UNESP]; Broetto, Fernando [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
The common bean is a sensitive plant to the effects of water deficit and physio-biochemical alterations, which influence the yield are observed. Vegetal biostimulants are inputs that present potential to mitigate the effects of water deficit on crop development. This paper aimed to evaluate the physiological and biochemical impact of water deficit on the common bean and the potential of applying biostimulants as a mechanism to tolerate stress. The assay was conducted in an agricultural greenhouse in Botucatu-Brazil, the pots were disposed in a split-plot design in randomized blocks, with four replications. The treatments in the plots corresponded to the water content tension, control (-10 kPa) and water deficit (-40 kPa), in the subplots the biostimulant treatments (B1-control; B2-Bacillus amyloliquefaciens BV; B3-Bacillus amyloliquefaciens BV 03 + algae extract Ascophyllum nodosum). The analyzed variables were leaf pigments, gas exchanges, total soluble proteins, L-proline, specific activity of the enzyme superoxide dismutase, shoot dry matter and crop yield. The water deficit negatively affected all parameters evaluated and the biostimulants in the tested form, did not show efficiency in helping the plants tolerate stress due to drought. We suggest new studies to prove the efficiency of biostimulants for field applications.
DESEMPENHO FISIOLÓGICO DO FEIJOEIRO SUBMETIDO A IRRIGAÇÃO DEFICITÁRIA E BIOESTIMULANTES
Keywords: Algae extract; Antioxidative metabolism; Leaf gas exchanges; Phaseolus vulgaris L; Plant growth-promoting bacteria